Association between childhood health, socioeconomic and school-related factors and effort-reward imbalance at work: a 25-year follow-up study - Wang, S; Sanderson, K; Venn, A; Dwyer, T; Gall, S (BMJ Publishing group, 2017)
Objectives Stress pathways can have origins in childhood but few early predictors have been explored in relation to adult job stress. This study examined whether childhood school, health or socioeconomic factors were associated with adult job stress. Methods Data came from the Childhood Determinants of Adult Health study that began in 1985 with children aged 7 to 15 years who reported effort-reward imbalance (ERI) scales at ages 31-41 years. Linear regression assessed the association between childhood factors and adult ERI adjusted for age and socioeconomic position (SEP) in childhood and adulthood. Results There were between 999 and 1,390 participants in each analysis. Lower adulthood ERI, indicating less job stress, was predicted by several school-related factors in men. For example, each higher category of learner self-concept was associated with a 19% (95%CI -32%, -6%) reduction in adult ERI and each unit increase in academic attainment was associated with a 15% (95%CI -28%, -3%) reduction in adult ERI. Childhood health was associated with adult ERI. For example, in women, overweight children had 14% (95% CI: 5%, 22%) higher adult ERI scores compared to healthy weight children and each unit of negative affect was associated with 2% (95%CI: 1%, 4%) increase in adult ERI. Adult SEP had no effect on these associations for men, but explained some of the effect in women. Childhood SEP had inconsistent associations with adult ERI. Conclusions Our findings suggests that a range of childhood socioeconomic, school- and health-related factors might contribute to the development of job stress in adulthood.